Juvenile socio-ecological environment shapes material technology in nest-building birds. (30th April 2020) - Breen, Alexis J; Lovie, Keren E; Guerard, Chloé; Edwards, Sophie C; Cooper, Jasmine; Healy, Susan D; Guillette, Lauren M
Abstract: Variation in animal material technology, such as tool use and nest construction, is thought to be caused, in part, by differences in the early-life socio-ecological environment—that is, who and what is around—but this developmental hypothesis remains unconfirmed. We used a tightly controlled developmental paradigm to determine whether adult and/or raw-material access in early life shape first-time nest construction in laboratory-bred zebra finches Taeniopygia guttata at sexual maturity. We found that juvenile access to both an unrelated adult and raw material of one color led to a majority preference (75%) by novice builders for this color of material over that for either natal-nest or novel-colored material, whereas a lack of juvenile access to both an unrelated adult and raw material led to a 4- and nearly 3-fold reduction in the speed at which novice builders initiated and completed nest construction, respectively. Contrary to expectation, neither the amount of time juveniles nor their adult groupmate spent handling the raw material appear to drive these early-life effects on zebra finches' first-time nest construction, suggesting that adult presence might be sufficient to drive the development of animal material technology. Together these data show that the juvenile socio-ecological environment can trigger variation in at least two critical aspects of animal material technology (material preference and construction speed), revealing a potentially powerful developmental window for technological advancement. Thus, to understand selection on animal material technology, the early-life environment must be considered. Abstract : Avian nest construction is a diverse animal material technology. We investigated how the environment in early life contributes to the development of nest construction in zebra finches under laboratory conditions. We found that whether an unrelated adult conspecific or raw material is present during juvenile adolescence affects the 1) material preference and 2) speed of building of birds when they reach sexual maturity and construct their first nest. Thus, the juvenile socio-ecological environment can promote variation in animal material technology.